DAMPAK BUDAYA LITERASI TERHADAP KARAKTER TANGGUNGJAWAB PESERTA DIDIK PADA ABAD 21 - Abustang, Perawati Bte; Maksum, Arifin; Nurhasanah, Nina (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
The application of a literacy culture can have an impact on strengthening the character of elementary school students. A literacy culture that is instilled early in elementary school can continuously form good character in elementary school children. This study aims to determine the impact of literacy culture on the responsible character of students in the 21st century. The research study was conducted using a quantitative approach using the ex post facto method. The population in this study were 87 students from SD Negeri Bawakareang I Makassar City from grades 4, 5 and 6, while the sample consisted of 55 students obtained by random sampling technique. The data collection method used a questionnaire and was analyzed using SPSS 21. The results of the descriptive analysis showed that a literacy culture of 55% was in the very influential category and the character of responsibility was in the very good category with a percentage value of 53. The results of the inferential analysis showed that there was an influence of literacy culture on the character of the participants' responsibilities students in the 21st century by obtaining a value of Sig 0.000 as determined by Sig (0.000) < (0.05) so that H0 is rejected and H1. The implications of this research are (1) Teachers should pay attention to the media used as teaching materials; (2) Students who are digitally literate must be motivated to develop their learning outcomes (3) A literacy culture can foster an interest in reading and have an impact on the character of responsibility; (4) For other researchers, they can conduct studies outside the culture of literacy and character of responsibility.